CAST CONCRETE MIXES FOR MONOLITHIC CONSTRUCTION - , В. В. (Municipal economy of cities. Series: «Economy science», 2013)
The results of studies aimed at obtaining udoboperekachivaemyh fine cast concrete mixes with a simultaneous decrease in water-cement ratio, designed for monolithic construction, as well as the results of experiments to determine the rheological properties of concrete mixtures of different compositions. The possibility of application of concrete mixes designed for pipeline transport.